(untitled) (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: The current study examined the effects of replacing Zea mays (maize) with solid-state Fermented cassava peel–foliage mix meal (FCPL) on the biochemical profiles and hematological markers. Materials and Methods: Cassava peels and foliage were processed by drying, grinding, and mixing at a ratio of 19:1; the resulting mixture was then fermented using Aspergillus niger American Type Culture Collection 16404. Then, broiler diets were supplemented with fermented cassava peel– foliage mix meal (FCPL) at 0%, 20%, 40%, and 60% maize replacement levels. In a fully randomized design, 480 seven-day-old Anak 2,000 broiler chicks were assigned to the four dietary treatments. Each treatment included 120 birds, which were then split into four duplicates of 30 chicks each. Results: Inclusion of FCPL tended to improve hematological parameters, with hematocrit (PCV) increasing significantly (p < 0.05) and peaking at 60% replacement, while erythrocyte count and hemoglobin concentration showed numerical increases. Aspartate aminotransferase (AST) and alkaline phosphatase (ALP) levels were lower in FCPL-fed groups, suggesting no negative effects on liver function, whereas serum cholesterol and glucose levels reduced significantly (p < 0.05) as FCPL inclusion increased. Total serum protein remained within normal physiological ranges, and albumin concentration was highest at 40% replacement, suggesting optimal protein utilization at this level. Conclusion: Replacing maize with up to 60% FCPL in broiler diets enhances PCV levels, reduces serum cholesterol, and supports liver function. These findings highlight fermented cassava by-products as a sustainable, health-promoting, and cost-effective alternative energy source in poultry nutrition, contributing to feed resource diversification and improved productivity. J. Adv. Vet. Anim. Res., 12(4): 1305–1313, December 2025 http://doi.org/10.5455/javar.2025.l991